Sensitivity of the early life stages of a mayfly to fine sediment and orthophosphate levels - Everall, Nicholas C.; Johnson, Matthew F.; Wood, Paul; Mattingley, Lauren (Elsevier, 2017)
The ecological effects of interacting stressors within lotic ecosystems have been widely acknowledged. In particular, the ecological effects of elevated fine sediment inputs and phosphate have been identified as key factors influencing faunal community structure and composition. However, while knowledge regarding adult and larval life stage responses to environmental stressors has grown, there has been very limited research on their eggs. In this study, the eggs of the mayfly Serratella ignita (Ephemerellidae: Ephemeroptera) were collected and incubated in laboratory aquaria to hatching under differing concentrations of inert suspended sediment (SS) and orthophosphate (OP), individually and in combination. Results indicate that SS and OP have greater effects on egg hatching in combination than when either were considered in isolation. SS displayed a greater effect on egg survival than OP in isolation or when OP was added to elevated SS treatments. Egg mortality in control treatments was around 6% compared to 45% in treatments with 25 mg 1⁻¹ SS and 52% in 0.3 mg 1⁻¹ OP treatments. Even relatively modest levels of each stressor (10 mg 1⁻¹ SS; 0.1 mg 1⁻¹ OP), below national legal thresholds, had significant effects on egg survival to hatching. The results support calls for legal levels of SS to be reassessed and suggest that more research is required to assess the impacts of pollution on invertebrate egg development given their different sensitivity and exposure pathways compared to other life stages.